2019
DOI: 10.1017/s146342361800097x
|View full text |Cite|
|
Sign up to set email alerts
|

Type 2 diabetes and physical activity: barriers and enablers to diabetes control in Eastern India

Abstract: Introduction: Type 2 diabetes (T2D) has tremendous morbidity burden owing to disease management and complication prevention. Behavior modification identified as a key to management includes healthy diet and regular physical activity (PA). This study aims to identify patterns and preferences of PA of T2D patients and explore perceived enablers and barriers for diabetes control in Bhubaneswar. Methods: Cross-sectional, facility-based study conducted in the private sector from June to Augus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…The participants specified the following factors were the obstacles in adopting lifestyle change recommendations, which are food accessibility, food habits, stress, lack of time, lack support and low motivation level. Some of the obstacles mentioned in Part B of the current study were in line with the results found in the previous studies (Al-Busaidi, 2008;Bunza and Alhassan, 2019;Sanghamitra et al, 2019). However, there were additional barriers found in Part B of the study, including good socioeconomic status and eating to please others.…”
Section: Discussionsupporting
confidence: 89%
“…The participants specified the following factors were the obstacles in adopting lifestyle change recommendations, which are food accessibility, food habits, stress, lack of time, lack support and low motivation level. Some of the obstacles mentioned in Part B of the current study were in line with the results found in the previous studies (Al-Busaidi, 2008;Bunza and Alhassan, 2019;Sanghamitra et al, 2019). However, there were additional barriers found in Part B of the study, including good socioeconomic status and eating to please others.…”
Section: Discussionsupporting
confidence: 89%
“…The results of this study reveal that people did not have the company to exercise. These findings are similar to the results of Sanghamitra et al (2019) and Van Dam et al (2005). Therefore, Sanghamitra et al (2019) Van Dam et al (2005 suggested that sensitizing social support in societies and taking support of family and friends could help promote the culture of physical activities in form of emotional reinforcement.…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, Sanghamitra et al (2019) Van Dam et al (2005 suggested that sensitizing social support in societies and taking support of family and friends could help promote the culture of physical activities in form of emotional reinforcement. Sanghamitra et al (2019) Van Dam et al (2005 have reported their effectiveness in controlling diabetes. This study investigates overlooked problems in T2DM patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although diabetics are often encouraged to exercise, they are usually less successful. Such that, some patients are unable to maintain their motivation to continue physical activity, and there are many personal and environmental barriers that cause instability in their physical activity [ 8 ]. As some studies show, sedentary lifestyle has been reported 60.1% in men with diabetes and 72.9% in women with diabetes [ 9 ].…”
Section: Introductionmentioning
confidence: 99%